The Spooky Politics of Dark Truths - Newton, Richard (Religion & theology, 2018)
As social theory garners cache in departments of Religious Studies, scholars find themselves unclear about how to address the notion of truth. This paper approaches truth as an opportunity to explain the role of truth-claims in erecting and razing social boundaries. It begins by reframing or "signifying on" Alan Race's typology of exclusivism, inclusivism, and pluralism in order to register social formations rather than soteriological criteria. Then it reviews moments in African American cultural history in order to explain the ways people mediate identity politics though truth-claims. Readers will visit three, race-centered debates over memorials on college campuses in the United States of America as case studies for demonstrating this perspectival shift. In so doing, the paper presents an alternative model for the kind of analytical social commentary Religious Studies scholars may provide their publics.